2002
DOI: 10.1002/glia.10167
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microglia: A neuroinflammatory role for CAP37

Abstract: Recent evidence suggests that inflammation and immune function in the central nervous system (CNS) may play a considerable role in the progression of many neurodegenerative diseases. It is known that microglia, the CNS equivalent of peripheral blood monocytes, may be instrumental in causing neurotoxicity. However, the mediator(s) that activates microglia to produce toxic substances that orchestrate cell death has yet to be elucidated. We have identified a novel inflammatory molecule, cationic antimicrobial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…Thus, HBP has to act directly on the macrophages as indicated by a rapid Ca 2+ mobilization. In line with the mechanism proposed by our data, an enhanced phagocytosis of zymosan by microglial cells in response to HBP was recently shown (33). This response was associated with enhanced expression of MHC class II (33), which is in agreement with the upregulation of HLA class II in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, HBP has to act directly on the macrophages as indicated by a rapid Ca 2+ mobilization. In line with the mechanism proposed by our data, an enhanced phagocytosis of zymosan by microglial cells in response to HBP was recently shown (33). This response was associated with enhanced expression of MHC class II (33), which is in agreement with the upregulation of HLA class II in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the mechanism proposed by our data, an enhanced phagocytosis of zymosan by microglial cells in response to HBP was recently shown (33). This response was associated with enhanced expression of MHC class II (33), which is in agreement with the upregulation of HLA class II in our study. The significance of our finding is further highlighted by observations in a murine disease model, in which it is reported that i.p.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment of macrophages with azurocidin enhanced the expression of HLA II, CD40, and CD86, in agreement with findings from microglial cells treated similarly [45]. Expression of these molecules is a sign of the classical macrophage activation being functionally related to enhanced antimicrobial effectiveness and a more powerful activation of the adaptive immune system [46].…”
Section: Azurocidin Activates Monocytes and Macrophagessupporting
confidence: 84%
“…In addition, in a murine model of fecal peritonitis, intraperitoneal application of azurocidin after cecal ligation and puncture improved survival, much of which was a result of increased recruitment of monocytes and enhanced phagocytic activity within macrophages [80]. Furthermore, enhanced phagocytosis by microglial cells has been demonstrated after treatment with azurocidin, indicating that this might be a general mechanism for macrophages [81].…”
Section: Reviewmentioning
confidence: 95%